PENGARUH BAKTERI ENDOFIT TANAMAN SAMAMA (Anthocephallus macropyllus) TERHADAP PERTAMBAHAN TINGGI DAN JUMLAH DAUN SEMAI TANAMAN GANDARIA (Bouea macrophylla) - Muhammad Gofal Yahya Tuharea; Johan M. Matinahoru; Fransina S. Latumahina (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Samama (Anthocephalus macrophyllus) and Gandaria (Bouea macrophylla) are plant species with significant ecological value. Seed germination success is a critical factor in plant nursery development. One approach to enhance germination is through the utilization of endophytic bacteria residing within plant tissues. This study aimed to determine the effect of endophytic bacteria derived from Samama on Gandaria seed germination. A Completely Randomized Design (CRD) was employed with two treatments without fertilizer (A0) and endophytic biofertilizer (A1) each with 10 replications (n = 20). Endophytic bacteria were isolated from Samama roots via 14-day fermentation and applied at a dose of 100 ml per plant to Gandaria seedlings. Observed parameters included plant height, leaf number, and bacterial identification on roots, analyzed using ANOVA and binomial test (Minitab 19). The results showed that endophytic bacteria from Samama, predominantly of the genus Bacillus, were successfully inoculated into Gandaria seedlings, increasing average plant height by 5 cm and leaf count by 4 leaves over two months. Bacterial identification in Gandaria seedlings further revealed the presence of two genera, namely Pseudomonas and Azospirillum.